The Pandemic Preferred User - Ellis, Katie; Kao, Kai-Ti; Pittman, Tim (University of Texas at Arlington Libraries, 2020)
As COVID-19 was declared a pandemic, universities acted quickly to move their core business of teaching and research online. Classes shifted to platforms such as Zoom, Webex, Collaborate and Microsoft Teams and teachers and students alike were expected to adapt. And they did. While there has been much discussion of the unpaid labour involved in making this shift and the difficulties inherent in merging work, study and domestic life, there has been little acknowledgement or analysis of inherent notions of the preferred user in this rapid shift to technology.